CSR Disclosure of Indonesia Energy Sector: Financial Performance, Firm Size, and Growth - Khoerunnisa, Syifa; Muslih, Muhammad (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Corporate social responsibility disclosure is a company activity in communicating the social and environmental impacts of the company's economic activities to stakeholders as a whole. This corporate social responsibility is disclosed in the company's sustainability report. The importance of corporate social responsibility disclosure for companies has been regulated in the Law. However, there are still many companies that do not publish sustainability reports as a form of awareness of CSR disclosure, so CSR disclosure is still relatively low. The purpose of this study is to analyze the effect of ROA, NPM, Current Ratio, DER, firm size, and growth on corporate social responsibility disclosure in Energy sector companies listed on the Indonesia Stock Exchange in 2020-2022. The method used in this study is a quantitative method, for sample selection using porposive sampling method. There were 72 observations from 24 companies. Data processing using panel data analysis techniques with Eviews 12 software. The results showed that the effect of ROA, NPM, Current Ratio, DER, firm size, and growth had a simultaneous effect on corporate social responsibility disclosure. Partially, ROA, NPM, and firm size affect corporate social responsibility disclosure. While Current Ratio, DER, and growth have no effect on corporate social responsibility disclosure. Keywords: Corporate Social Responsibility Disclosure, Return On Assets, Net Profit Margin, Current Ratio, Debt of Equity Ratio, Firm Size, and Growth